PENGARUH PERBESARAN JUMLAH ELEKTRODA TERHADAP TEGANGAN TEMBUS PADA DIELEKTRIK UDARA MENGGUNAKAN SUMBER TEGANGAN TINGGI AC - Satria, Muchamad Iqbal; Dhofir, Moch.; Nurwati, Tri (Jurnal Mahasiswa TEUB, 2024)
Based on the law of enlargement, the probability value of breakdown voltage in conductor insulation is influenced by changesin the size or number of conductor arrangements. This change affects the insulation application standards that will be appliedto high voltage equipment. This research describes the effect of increasing the number of electrodes on the probability ofbreakdown voltage in air dielectrics using high voltage AC. The research method used is to collect data through testingbreakdown voltage and leakage current at the High Voltage and Applications Laboratory of Brawijaya University, as well assimulating electric field distribution with FEMM 4.2 software. Variations in the electrode arrangement of the rods used are1 pair, 2 pairs, 3 pairs, 4 pairs, and 5 pairs. Breakdown voltage testing was carried out using the Up and Down method in40 trials and analyzed based on the Normal Distribution graph (Gaussian). The results obtained from this research are theinfluence of increasing the number of electrode arrays on the breakdown voltage probability value, where the greater thevalue of increasing the number of electrodes, the greater the breakdown voltage probability value at the same voltage. Thevalue of the leakage current between the electrode arrays increases as the number of arrays applied increases. This causesthe air resistance value between the electrode arrays to decrease as the amount applied increases. Keywords: Breakdown voltage; Leakage current; Probability; Enlargement law; Electric field